STOCHASTIC PROGNOSTIC PARADIGM FOR PETROCHEMICAL PIPELINES SUBJECT TO FATIGUE - Jaoude, Abdo Abou; El-Tawil, Khaled (American journal of engineering and applied sciences, 2013)
The most important aim for industrialists is the prevention and the evaluation of their products state since non-predicted failure is very expensive in some cases. This can be done mainly by the evaluation of the "Remaining Useful Lifetime" (RUL) by the means of prognostic approaches compensating the inconveniences of classical maintenance strategies. A proposed analytic prognostic methodology based on damage laws, such as Paris-Erdogan's and Palmgren-Miner's laws, is developed here to determine the RUL of the system. It permits to ensure a high availability and productivity with less cost for industrial systems. To make this approach more reliable, it is essential to introduce the stochastic description. For the case of fatigue effect where damage state is growing from macro-cracks to total failure, D(N) expresses an increasing scalar damage function in terms of loading cycles N. The RUL is estimated from a predefined threshold of damage D sub( c). Pipelines tubes, subject to fatigue effects due to pressure-depression alternation, belong to vital mechanical systems in petrochemical industries that serve to transport natural gases or liquids. The prognostic evaluation of their states increases the tubes availability while minimizing their missions cost.